Association between witnessing physical violence between parents and intimate partner violence against Bolivian men: A national cross-sectional analysis of the 2016 demographic and health survey - J. Matias Bardales-Rodríguez; Flavia Rioja-Torres; Akram Hernández-Vásquez; Diego Azañedo (Preventive Medicine Reports)
Objective: Assess the association between having witnessed physical violence between parents and intimate partner violence (IPV) against men in Bolivian adults according to the Encuesta de Demografia y Salud (EDSA) 2016. Methods: A retrospective cross-sectional study was conducted using data from the EDSA 2016 in Bolivia. The variable of interest in this study was IPV in men experienced during the last 12 months (any type of violence, physical and/or sexual, and psychological). The exposure variable was having witnessed physical violence between parents. Unadjusted and adjusted generalized linear models were constructed to assess the association of interest, and prevalence ratios (PR) with 95 % confidence intervals (95 %CI) were reported. Results: Witnessing physical aggression between parents in childhood was associated with a greater probability of suffering intimate partner violence in adulthood (adjusted PR [aPR]: 1.50; 95 %CI: 1.34–1.69). Similarly, the presence of physical aggression between parents in childhood was associated with a higher probability of physical and/or sexual violence (aPR: 1.92; 95 %CI: 1.53–2.39) and psychoverbal violence (PR: 1.48; 95 %CI: 1.32–1.67). The association identified was not modified by having suffered violence during childhood. Conclusions: Participants who witnessed physical violence between parents were more likely to suffer intimate partner violence (IPV), psycho-verbal violence and physical and/or sexual violence by their partners.